Electrochemical Optimizing of SSC-SDCC Cathodes for LT-SOFCs: Synergistic Control of Composition, Phase Structure, Morphology, and Thermal Properties - Sufizar Ahmad,; Umira Asyikin Yusop,; Siti Fairus Mohammad,; Hamimah Abd Rahman,; Dedikarni Panuh,; Joko Sedyono, (International Journal of Integrated Engineering, 2025)
The growing global demand for alternative energy sources has driven the development of solid oxide fuel cells (SOFCs), which offer efficient and eco-friendly energy conversion. However, conventional SOFCs high operating temperatures accelerate material degradation, necessitating the exploration of low-temperature SOFC (LT-SOFC) materials. This study investigates samarium strontium cobalt-samarium doped ceria carbonate (SSC-SDCC) composite cathodes with varying weight ratios (50:50, 60:40, and 70:30, denoted as SSCB55, SSCB64, and SSCB73) mixed via high-energy ball milling (HEBM). The powders were calcined at 750°C, pelletised using the uniaxial pressing method, and sintered at 600°C. X-ray diffraction (XRD) analysis confirmed the formation of the SrCO? secondary phase, despite of this phase formation, the cathode exhibited enhanced performance with reduce ASR values. The energy dispersive spectroscopy (EDS) mapping demonstrated uniform elemental distribution across all samples, ensuring compositional homogeneity. The field emission scanning electron microscopy (FESEM) revealed microstructural evolution, including increased agglomeration after calcination process. Porosity measurement (31-44%) aligned with optimal cathode material requirements, facilitating efficient gas diffusion and electrochemical reactions. Thermal expansion coefficient (TEC) analysis indicated that only SSCB55 exhibited acceptable compatibility with the SDCC electrolyte, whereas SSCB64 and SSCB73 exceeded the recommended thresholds, risking mechanical failure during thermal cycling. Electrochemical impedance spectroscopy (EIS) further revealed that the SSCB55 cathode achieved low area specific resistance (ASR) by 5.06 Wcm2 at 600°C, indicating superior oxygen reduction reaction (ORR) kinetics and highlighting its potential for LT-SOFC applications. These findings suggest that optimised SSC-SDCC composites, particularly SSCB55, are promising candidates for high-performance LT-SOFC cathodes.